Seed Density, Seed Germination Performance On Various Substrates And The Effects Of Iba (Indole-3-Butyric Acid) On Stem Cutting Of Eucalyptus Pellita - Muslim, Marlinah (2023)
The main objective of this research is to propose a seedling production technique to be applied by the local community to support the Eucalyptus pellita-based industry in Malaysia. Eucalyptus spp. which includes E. pellita is a key plant to several industries such as the paper and furniture industries, both for local and global use.